2017
DOI: 10.1177/0972063417699692
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Scale to Measure Obstetric and Gynaecology Professionals’ Attitudes towards Medical Termination of Pregnancy and Emergency Contraception Services, Kerala, India

Abstract: Medical termination of pregnancy (MTP) services and emergency contraceptive pills (ECPs) are legal in India. Despite this, there are barriers to women’s access due to provider resistance towards these services. It is important to understand the obstetrics and gynaecology professionals’ (OGPs) attitudes towards MTP and ECP services. The Achutha Menon Centre for Health Science Studies (AMCHSS) scale with 20 items, 16 related to MTPs and 4 related to ECPs, was developed and validated to measure the attitude of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Data concerning provider knowledge was available in some studies [ 25 , 28 , 31 , 34 , 37 - 41 ]. While most providers surveyed felt ECP was safe [ 28 , 35 , 42 ] more than half of participants in some studies held reservations [ 30 , 34 , 37 , 41 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data concerning provider knowledge was available in some studies [ 25 , 28 , 31 , 34 , 37 - 41 ]. While most providers surveyed felt ECP was safe [ 28 , 35 , 42 ] more than half of participants in some studies held reservations [ 30 , 34 , 37 , 41 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…A lack of understanding of the biological mechanism of action underpinning ECP was noted among many study respondents; some were not aware of the disruption of ovulation or said that ECP blocks the implantation of the fertilized ovum, or were not sure of the mechanism [ 30 , 42 - 44 ]. Some providers described ECP as an abortifacient [ 29 , 37 , 39 , 40 , 42 , 43 , 45 - 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Achutha Menon Centre for Health Science Studies abortion scale 19 tool was used to assess the health providers' attitudes towards safe abortion. The tool had the following sections.…”
Section: Methodsmentioning
confidence: 99%
“… 18 Various studies done among health providers in Chhattisgarh, Meghalaya, Uttarakhand, and Kerala showed that a high proportion harbored a negative attitude. 11 , 13 , 14 , 19 Moreover, inaccurate or inadequate information on the part of providers especially with respect to newer techniques such as medical abortion constitutes a significant challenge to abortion access in India.…”
Section: Introductionmentioning
confidence: 99%